Strategi Kebijakan dalam Memaksimalkan Pemanfaatan Potensi Panas Bumi Untuk Ketahanan Energi dan Transisi Hijau Indonesia - Wulandari, Titik (Jurnal Locus Penelitian dan Pengabdian, 2026)
This policy paper analyzes strategies to maximize the utilization of Indonesia's geothermal potential to support energy security and the green transition, with a focus on addressing the root cause of the low exploration success rate due to the lack of integrated geoscience data. Through a comprehensive policy analysis method involving regulatory inventory, data tabulation, and expert assessment, this study identifies the Establishment of a Geoscience Survey Institute and a Geothermal Endowment Fund as the most strategic solution with a priority score of 4.4. This policy is designed to provide integrated baseline data that can reduce exploration risks by up to 50%, cut costs by up to 40%, and accelerate project development by 2-3 years. Its implementation requires a comprehensive regulatory framework that includes an institutional legal umbrella, endowment fund management, data integration, and a robust monitoring and evaluation system. Using a logic model approach, this policy is projected to support the achievement of the 6.4 GW geothermal capacity target by 2030, contribute to a reduction in GHG emissions of 35 million tons CO2e/year, while strengthening national energy security based on domestic resources.